Combating iron and zinc malnutrition through mineral biofortification in maize through plant growth promoting Bacillus and Paenibacillus species - Ahmad, Maqshoof; Hussain, Azhar; Dar, Abubakar; Luqman, Muhammad; Ditta, Allah; Iqbal, Zafar; Ahmad, Hafiz Tanvir; Nazli, Farheen; Soufan, Walid; Almutairi, Khalid; Sabagh, Ayman El (Frontiers in Plant Science, 2023)
The burgeoning population of the world is causing food insecurity not only by less food availability but also by the malnutrition of essential nutrients and vitamins. Malnutrition is mostly linked with food having micronutrients lower than the optimal concentration of that specific food commodity and becoming an emerging challenge over the globe. Microbial biofortification in agriculture ensures nutritional security through microbial nitrogen fixation, and improved phosphate and zinc solubilization, which increase the uptake of these nutrients. The present study evaluates the novel plant growth-promoting rhizobacteria (PGPR) to biofortify maize gain. For this purpose, a pot and two field experiments for maize were conducted. PGPRs were applied alone and in combination for a better understanding of the biofortification potential of these strains. At physiological maturity, the growth parameters, and at harvest, the yield, microbial population, and nutritional status of maize were determined. Results revealed that the consortium (ZM27+ZM63+S10) has caused the maximum increase in growth under pot studies like plant height (31%), shoot fresh weight (28%), shoot dry weight (27%), root fresh (33%) and dry weights (29%), and microbial count (21%) in the maize rhizosphere. The mineral analysis of the pot trial also revealed that consortium of ZM27+ZM63+S10 has caused 28, 16, 20, 11 and 11% increases in P, N, K, Fe, and Zn contents in maize, respectively, as compared to un-inoculated treatment in pot studies. A similar trend of results was also observed in both field trials as the consortium of ZM27+ZM63+S10 caused the maximum increase in not only growth and biological properties but also caused maximum biofortification of mineral nutrients in maize grains. The grain yield and 1000-grain weight were also found significantly higher 17 and 12%, respectively, under consortium application as compared to control. So, it can be concluded from these significant results obtained from the PGPR consortium application that microbial inoculants play a significant role in enhancing the growth, yield, and quality of the maize. However, the extensive evaluation of the consortium may help in the formulation of a biofertilizer for sustainable production and biofortification of maize to cope with nutritional security.